Teachers' perception in medical university towards online assessment of students conducted during the COVID-19 pandemic - Bharti Nigam; Luxmi Singh; Sonal Gupta (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: During this COVID-19 pandemic a large number of institutes have undertaken an online assessment of medical students such as zoom meets, online objective structured clinical examination [OSCE] google forms, etc. The present study was undertaken to determine the perceptions and opinions of teachers towards online assessment so as to plan the future strategy regarding the assessment system. Materials & Methods: An online questionnaire was validated and distributed among 120 teaching faculty of a tertiary care hospital in North India and informed consent was obtained. It consisted of standard Likert scale questions which comprised 22 questions. The questionnaire was grouped into 4 categories: demographics, Comparison between traditional and online assessment, Advantages and limitations, different teaching methods, and acceptance of online assessment. The responses were collected and analyzed by using descriptive analyses. Result: The mean age was 41.25 ± 9.35 out of which the majority were females (55%). Most teachers found online exams less stressful, within the COVID norms, and more comfortable. The main limitation was no interaction between the patients & students followed by poor internet connection. 70.30% of the teaching faculty prefers traditional face-to-face assessment to online assessment, 23.40% select the blended mode, and only 6.30% of teachers prefer online assessment. Conclusion: The results from our study depicted that 70% of the teaching faculty prefer traditional assessment. The responses provided us with the viewpoint of the medical institute's teaching faculty, which will help us improve the logistic of the assessment program.